2023
DOI: 10.1002/cplu.202300009
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Photodynamic Therapy for the Remote Eradication of Bacteria

Abstract: The emergence of multi‐drug resistant bacteria strains has been an uphill battle in modern healthcare worldwide, due to the increasing difficulty of killing them. The evolving pathogenicity of bacteria has led to researchers searching for more effective antimicrobial therapeutics to successfully eliminate them without undesirable consequences to the human body. In recent years, antimicrobial photodynamic therapy (APDT), an obsolete technique for cancer treatments, has been reported to eradicate bacteria and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 215 publications
(369 reference statements)
0
6
0
Order By: Relevance
“…During antibacterial PDT, type I and type II reactions can occur simultaneously, and the ratio between these processes depends on the type of PS utilized, its chemical structure and the specific microenvironment in which the PDT is implemented. The interplay between type I and type II mechanisms is a critical factor to consider for an optimized treatment and understanding its underlying photochemical processes [88][89][90]. As already reported, ROS are detrimental for bacteria by targeting several vital microbial molecules, such as proteins, lipids, and nucleic acids, thus determining bacterial death.…”
Section: Basic Principles Of Photodynamic Therapymentioning
confidence: 99%
“…During antibacterial PDT, type I and type II reactions can occur simultaneously, and the ratio between these processes depends on the type of PS utilized, its chemical structure and the specific microenvironment in which the PDT is implemented. The interplay between type I and type II mechanisms is a critical factor to consider for an optimized treatment and understanding its underlying photochemical processes [88][89][90]. As already reported, ROS are detrimental for bacteria by targeting several vital microbial molecules, such as proteins, lipids, and nucleic acids, thus determining bacterial death.…”
Section: Basic Principles Of Photodynamic Therapymentioning
confidence: 99%
“…These materials are becoming important as a promising solution for wound management due to their tunability, softness, permeability, biocompatibility, or biodegradability. In the context of drug delivery, hydrogels benefit from their porosity, which enables drug encapsulation within a 3D polymeric network. Some antibacterial hydrogels have been particularly valuable in the context of light-induced therapies such as antimicrobial photodynamic therapy (aPDT). aPDT combines light, molecular oxygen, and a photosensitizer to generate reactive oxygen species (ROS) that oxidize lipids, proteins, DNA, and other biomolecules, leading to bacterial inactivation. Good transparency is, therefore, needed for hydrogels to perform well in aPDT, especially for wound dressing applications, and previous work has focused on optimizing their optical properties. , It was shown that electron-beam polymerized polyethylene glycol diacrylate (PEGDA) hydrogels have a higher transmittance over a broader wavelength range compared to their UV-cured counterparts, reaching values well above 90% …”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] The main principle behind aPDT's antibacterial effect is based on the light-driven Reactive Oxygen Species (ROS) generation of a light-responsive molecule (termed a photosensitizer). [19,20] In PDT, transition metal complexes have generated a new regime and direction. [21][22][23][24][25][26][27][28] For example, TLD1433 is in clinical trials as a PDT agent to treat bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, antibacterial photodynamic therapy (aPDT) has emerged as a non‐invasive and alternate therapeutic modality to overcome antibacterial drug resistance issues [15–18] . The main principle behind aPDT′s antibacterial effect is based on the light‐driven Reactive Oxygen Species (ROS) generation of a light‐responsive molecule (termed a photosensitizer) [19,20] . In PDT, transition metal complexes have generated a new regime and direction [21–28] .…”
Section: Introductionmentioning
confidence: 99%